The Image of The Priangan Woman in The Wanodja Wirayudha Dance - Rahayu Cahyaning Tyas; Ayo Sunaryo; Ria Sabaria (Universitas Negeri Semarang, 2023)
Behind the presentation of dance, it does not only reveal the aesthetics of movement but also reveals social aspects that describe a condition or event in society, one of which is the Wanodja Wirayudha dance, which has an image related to the image of the Priangan woman which is actualized in the form of movement, clothing, make-up, to dance property used. Wanodja Wirayudha dance is a creative dance created by the choreographer of a studio in West Bandung Regency which was inspired by the historical events of female heroes in the city of Bandung. This study aims to describe the image of the Priangan woman depicted in the Wanodja Wirayudha dance. The method used is a descriptive analysis method with a qualitative approach. The results of this study were obtained from interviews and documentation studies. The findings of this study indicate that the image of the Priangan woman that is revealed in the Wanodja Wirayudha dance is talking about a female figure who has courage, strong personality, toughness, and a patriotic spirit like the Priangan woman as a hero. This research will provide data and information that can be used in further research studies related to the image of women in the wanodja wirayudha dance.